2024
DOI: 10.1109/tnnls.2023.3242345
|View full text |Cite
|
Sign up to set email alerts
|

The Symplectic Adjoint Method: Memory-Efficient Backpropagation of Neural-Network-Based Differential Equations

Abstract: The combination of neural networks and numerical integration can provide highly accurate models of continuoustime dynamical systems and probabilistic distributions. However, if a neural network is used n times during numerical integration, the whole computation graph can be considered as a network n times deeper than the original. The backpropagation algorithm consumes memory in proportion to the number of uses times of the network size, causing practical difficulties. This is true even if a checkpointing sche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Augmented Neural ODEs [14] extended Neural ODEs by using the additional dimensions to learn more complex functions. Matsubara et al [21] improved Neural ODEs via the symplectic adjoint method and demonstrated that the symplectic adjoint method consumes much less memory than the naive backpropagation algorithm and checkpointing schemes, performing faster than the adjoint method.…”
Section: Reconsidering Dnns From the Perspective Of Dynamic Systemsmentioning
confidence: 99%
“…Augmented Neural ODEs [14] extended Neural ODEs by using the additional dimensions to learn more complex functions. Matsubara et al [21] improved Neural ODEs via the symplectic adjoint method and demonstrated that the symplectic adjoint method consumes much less memory than the naive backpropagation algorithm and checkpointing schemes, performing faster than the adjoint method.…”
Section: Reconsidering Dnns From the Perspective Of Dynamic Systemsmentioning
confidence: 99%
“…Neural networks are a type of typical supervised learning methods, which can effectively overcome the limitations of linear models by learning the non-linear mapping between inputs and outputs [14][15][16][17]. Neural networks are composed of some functions associated with a directed graph.…”
Section: Neural Networkmentioning
confidence: 99%
“…Backpropagation [15,16] is a widely used training strategy. It utilises the derivative chain rule in order to obtain the weights of each layer.…”
Section: Neural Networkmentioning
confidence: 99%
See 2 more Smart Citations